Love, the law and religion: : Dangerous liaisons - De Witt, Theo (Stellenbosch Theological Journal, 2021)
To the question "Are we as humans obliged to something because it is good, or because it is prescribed by God?", the Christian Church father Tertullian answered: we obey because of God's will. Today, many are inclined to give the first answer, and even to distrust people who follow Tertullian. In this article, however, the author demonstrates the continuing relevance of Tertullian's paradigm about reason/will in modern political philosophy: for example, in Thomas Hobbes'"decisionista" maxim: not truth, but the will of formal authority establishes the law. Or in the democratic combination of rational discussion and decisive majority will. This gives modern democracy the character of a ritual instead of a rational machinery: a kind of secular divine judgement. Also another issue allows us to demonstrate the lasting actuality of Tertullian's paired concepts: the issue that a political community not only needs democratic legitimacy, but also national unity. Here also the relationship with the question of violence becomes relevant. The author presents four "dangerous liaisons" between love and rational justice. The basic intuition here is that we "not only want to live in a world which we are able to consider just, but in a reality which we experience as valuable in and of itself" (Paul W. Kahn). Love can strengthen rational justice, and vice versa; love can get in conflict with justice; justice can try to expand itself at the expensive of love; and “the other way around“ love can drive us to the universal and transcend legal boundaries. As a conclusion, we can distinguish clearly between nationalism and patriotism. And second, we must admit that, while love will always destabilize law, the opposite is also true: we have to make calculations, so that justice can also destabilize love.